Penerapan Metode A*Star Pada Pencarian Rute Tercepat Menuju Ke Sekolah Tinggi Ilmu Komputer Cipta Karya Informatika (Stikom Cki): Finding the Nearest Route From Location To Destination Location - Raya Fitri Boangmanalu; Tri Wahyudi (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The College of Computer Science Cipta Karya Informatics (STIKOM CKI) is an educational institution that provides academic degrees in the field of technology or computers. STIKOM CKI has two study programs for undergraduate level (S1), namely: informatics engineering and information systems. STIKOM CKI was established on September 5, 2002, by the Decree of the Minister of National Education No.: 204/D/O/2002. Which is located on Jl. Raden Inten II No.8, RT.5/RW.14, Duren Sawit, Kec. Duren Sawit, East Jakarta City, Special Capital Region of Jakarta 13440. To get to the STIKOM CKI campus, students usually use motorbikes or public transportation. However, there are some students whose homes are far to get to campus, it takes about 1 hour or more if there are traffic jams, they can reach campus in about 1 hour and a half. In its application, the A*Star algorithm uses distance as the best value calculation process. With the application of the A*Star algorithm, the information on determining the fastest path will be more accurate because this method selects the side with the minimum weight. In addition, the purpose of this research is to be able to provide information about the location of the STIKOM CKI campus with the fastest route so that it can help users to choose the fastest route so that they can arrive at the location as well as to provide information on the nearest path based on the results of the A*Star algorithm calculations applied in this study. . Keywords— Game Elements, Grammar English, Learning Applications